Assessment of Patients with a DePuy ASR Metal-on-Metal Hip Replacement: Results of Applying the Guidelines of the Spanish Society of Hip Surgery in a Tertiary Referral Hospital - Jenaro Fernández-Valencia; Xavier Gallart; Guillem Bori; Sebastián Garcia Ramiro; Andrés Combalía; Josep Riba (Advances in Orthopedics)
The prognosis associated with the DePuy ASR hip cup is poor and varies according to the series. This implant was withdrawn from use in 2010 and all patients needed to be assessed. We present the results of the assessment of our patients treated with this device, according to the Spanish Society of Hip Surgery (SECCA) algorithm published in 2011. This retrospective study evaluates 83 consecutive ASR cups, followed up at a mean of 2.9 years. Serum levels of chromium and cobalt, as well as the acetabular abduction angle, were determined in order to assess their possible correlation with failure, defined as the need for revision surgery. The mean Harris Hip Score was 83.2 (range 42–97). Eight arthroplasties (13.3%) required revision due to persistent pain and/or elevated serum levels of chromium/cobalt. All the cups had a correct abduction angle, and there was no correlation between elevated serum levels of metal ions and implant failure. Since two previous ASR implants were exchanged previously to the recall, the revision rate for ASR cups in our centre is 18.2% at 2.9 years.